Antibiotic growth promoters and waxy corn enhance broiler growth performance through starch digestibility and microbiota modulation in the crop and ileum - Xu, Yanwei; Xiao, Yong; Ai, Chunxiao; Huang, Yihong; Zhou, Huajin; Li, Jianhui; Yuan, Jianmin (Poultry science, 2025)
This study aimed to investigate the internal connections between starch digestion properties and microbial changes in the gastrointestinal tract of broiler chickens. A total of 240 male AA+ broilers (21-day-old) were allocated to 4 treatments of regular and waxy corn with and without virginiamycin (6.4 g/t) in a 2 × 2 factorial arrangement. On day 35, growth performance and apparent starch digestibility were determined, and hormones in the serum and microbial profiles in the crop and ileum were analyzed. The results indicated that dietary starch was primarily digested in the jejunum of broiler chickens, and broilers receiving waxy corn exhibited significantly greater digestibility of both total starch and amylopectin in the distal jejunum, along with an improved feed-to-gain ratio (F/G) and European performance index (EPI), compared with the regular corn group (P< 0.05). Notably, virginiamycin significantly enhanced the amylose digestibility in the distal ileum and improved the F/G ratio (P< 0.05). Microbial analyses revealed that corn type did not affect microbial diversity in the crop and ileum. However, virginiamycin significantly reduced alpha diversity in the crop (Chao1: 129.63 vs. 191.14, P < 0.05) and ileum (observed species: 137.23 vs. 316.43, P < 0.05), and elevated Lactobacillus abundance (positively correlated with amylose digestibility, P < 0.001). In summary, waxy corn enhanced jejunal starch hydrolysis via its high amylopectin content, whereas virginiamycin promoted amylose digestion in the distal small intestine by selectively enriching the starch-degrading microbiota.